EFEKTIVITAS BABY MASSAGE MENGGUNAKAN VIRGIN COCONUT OIL (VCO) TERHADAP PENINGKATAN KUALITAS TIDUR BAYI USIA 1-10 BULAN DI PMB K KELURAHAN PASIR PUTIH KOTA DEPOK TAHUN 2022 - Febriana, Tyas (Journal of Midwifery Tiara Bunda, 2022)
Background: Sleep and rest are important components in baby development. Babies need fourteen hours of sleep a day. The body will release 75% of growth hormone when the baby sleeps. According to WHO data (2018), the prevalence of sleep disorders in babies in the world is 33% who experience sleep problems. Meanwhile, the prevalence of sleep problems in Indonesia is quite large, with 44.2% of babies experiencing sleep problems such as frequently waking up at night. Baby massage will make the baby sleepier and increase alertness or concentration. The increase in the length of a baby's sleep, which is an indicator of the quality of a baby's sleep due to massage, is caused by an increase in serotonin secretion levels produced during massage. Massage therapy using virgin coconut oil has no side effects on babies. Applying Virgin Coconut Oil to the skin keeps the baby warm and reduces body heat loss which results in the baby sleeping more soundly. Research Purposes: To determine the effectiveness of baby massage Virgin Coconut Oil in improving sleep quality in babies aged 1-10 months in PMB K, Pasir Putih Subdistrict, Depok City in 2022. Research Method: The type of research used is Pre Experiment Design using one group pre-posttest control group design. Research results: p-Value is 0.000 < α (0.05), so the H0 data is rejected and Ha is accepted. Conclusion: Baby Massage using Virgin Coconut Oil is effective in improving the sleep quality of babies aged 1-10 months in PMB K, Pasir Putih Village, Depok City in 2022.